STUDI ORIENTASI PEMASANGAN PANEL SURYA POLY CRYSTALLINE SILICON DI AREA UNIVERSITAS RIAU DENGAN RANGKAIAN SERI-PARALEL - Ridho Ravita Wardy; Krisman '; Cahyo Budi Nugroho (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
A research has been conducted on the study of the orientation of the criystalline poly silicon solar panel installation at the University of Riau area using a series - parallel circuit. The research was conducted from June 1 to June 14 2014 using solar panels of 4 types of poly silicon criystalline that were arranged in parallel using a series - parallel circuit. From the results of this study, the optimal time and angle of the poly crystalline silicon solar panel was at 09:00 pm at coordinates 00 0 .28.661' LU 101 0 .22.554' BT with elevation angle of 129.36 0 . The power generated was 34.2907 Watt. The power generated by the solar panels was influenced by the temperature, the higher the temperature was the smaller the power generated. Power output of solar panels was influenced by weather conditions. The power generated by the solar panels in sunny weather was greater than that was on a cloudy day. The average power for 14 days was 21,17862 Watt.